The effect of marketing mix and product quality on consumer satisfaction on purchase of dairy product - Budi Permana Yusuf; Edi Setiawan; Rakha Tri Kurnia (Universitas Negeri Padang, 2021)
The purpose of this study was to study the effect of marketing mix and product quality on consumer satisfaction in purchasing Frisian Flag Milk products at Indomart Halim Perdana Kusuma, East Jakarta. A questionnaire survey collected 90 research respondents. The data analysis used in this research is validity test, reliability test, descriptive statistical analysis, multiple linear regression analysis, classical assumption test, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing at the level of confidence (α = 0.05). The results of the study partially show that there is a positive and significant influence between the Marketing Mix on Consumer Satisfaction. While the product quality variable has a positive and significant influence on consumer satisfaction.